Measuring the insulating power from the sound impact of the floor covering of pressed expanded polystyrene - Adžić, Stefan; Radičević, Branko; Bjelić, Mišo; Šimunović, Dragiša; Marašević, Miljan; Stojić, Nenad (Journal of Production Engineering, 2023)
The paper presents a study of the change in the sound of the impact for two in practice the most commonly used thickness of the floating floor from expanded pollistyrene. The standard SRPS ISO 717-2 defines Normalized values of the level of impact sound per Terce for the reference ceiling, and the procedure for obtaining an authoritative reduction of the sound level of impact of floor covers. The addition of expanded polystyrene panels to the reinforced concrete ceiling was evaluated for the improvement of sound insulation according to the SRPS EN ISO 717-2 standard. The results of the research showed that by increasing the thickness of the layer of pressed expanded polystyrene there is an improvement in the insulation from the sound of the impact.